Comparison of myocardial contrast echocardiography with NC100100 and 99mTc sestamibi SPECT for detection of resting myocardial perfusion abnormalities in patients with previous myocardial infarction. Issue 5 (1st May 2000) - Jucquois, I; Nihoyannopoulos, P; D'Hondt, A-M; Roelants, V; Robert, A; Melin, J A; Glass, D; Vanoverschelde, J-L J
Abstract : OBJECTIVE: To determine whether myocardial contrast echocardiography (MCE) following intravenous injection of perfluorocarbon microbubbles permits identification of resting myocardial perfusion abnormalities in patients who have had a previous myocardial infarction. PATIENTS AND INTERVENTIONS: 22 patients (mean (SD) age 66 (11) years) underwent MCE after intravenous injection of NC100100, a novel perfluorocarbon containing contrast agent, and resting 99m Tc sestamibi single photon emission computed tomography (SPECT). With both methods, myocardial perfusion was graded semiquantitatively as 1 = normal, 0.5 = mild defect, and 0 = severe defect. RESULTS: Among the 203 normally contracting segments, 151 (74%) were normally perfused by SPECT and 145 (71%) by MCE. With SPECT, abnormal tracer uptake was mainly found among normally contracting segments from the inferior wall. By contrast, with MCE poor myocardial opacification was noted essentially among the normally contracting segments from the anterior and lateral walls. Of the 142 dysfunctional segments, 87 (61%) showed perfusion defects by SPECT, and 94 (66%) by MCE. With both methods, perfusion abnormalities were seen more frequently among akinetic than hypokinetic segments. MCE correctly identified 81/139 segments that exhibited a perfusion defect by SPECT (58%), and 135/206 segments that were normally perfused by SPECT (66%). Exclusion of segments with attenuation artefacts (defined as abnormal myocardial opacification or sestamibi uptake but normal contraction) by either MCE or SPECT improved both the sensitivity (76%) and the specificity (83%) of the detection of SPECT perfusion defects by MCE. CONCLUSIONS: The data suggest that MCE allows identification of myocardial perfusion abnormalities in patients who have had a previous myocardial infarction, provided that regional wall motion is simultaneously taken into account.